Insight into the evolution of the Solanaceae from the parental genomes of Petunia hybrida - Bombarely, Aureliano; Moser, Michel; Amrad, Avichai; Bao, Manzhu; Bapaume, Laure; Barry, Cornelius S.; Bliek, Mattijs; Boersma, Maaike R.; Borghi, Lorenzo; Bruggmann, Rémy; Bucher, Marcel; D'Agostino, Nunzio; et al. (Nature Publishing Group, 2016)
Petunia hybrida is a popular bedding plant that has a long history as a genetic model system. We report the whole-genome sequencing and assembly of inbred derivatives of its two wild parents, P. axillaris N and P. inflata S6. The current assemblies include 91.3% and 90.2% coverage of their diploid genomes (1.4 Gb; 2n=14) containing 32,928 and 36,697 protein-coding genes, respectively. The Petunia lineage has experienced at least two rounds of paleohexaploidization, the older gamma hexaploidy event, which is shared with other Eudicots, and the more recent Solanaceae paleohexaploidy event that is shared with tomato and other Solanaceae species. Transcription factors that were targets of selection during the shift from bee- to moth pollination reside in particularly dynamic regions of the genome, which may have been key to the remarkable diversity of floral color patterns and pollination systems. The high quality genome sequences will enhance the value of Petunia as a model system for basic and applied research on a variety of unique biological phenomena.